Relación familia-escuela desde la corresponsabilidad (2021)
The family and the school united in the joint responsibility of their parts, through cooperation and a good understanding of them, allows to facilitate the educational processes of children and students, finding happiness and at the same time the sense of their fulfillment, in this sense, family and school united for the well-being of their children for better results. Objective: To transform the family-school relationship from the co-responsibility of parents, teachers and sixth grade students (6) of the Simón Bolívar headquarters of the IEDT Francisco de Paula Santander of Fundación Magdalena. Methodology: This research has a qualitative approach and given its nature, we opted for Action Research. The data was collected through surveys, semi-structured interviews, group discussion and their analysis. Conclusions: The main results of this research object serve as the foundation for making more correct decisions by the teaching directors, teachers and parents regarding how to transform the family-school relationship, which must responsibly assume the commitment to prevail by the importance of this relationship, consolidating the parents' school as an instrument to train and educate in co-responsibility, among other issues, and not as a wasted space or in this case, even forgotten, that contributes to the development of the student's training process and its projection as part of a society that generates significant changes.